Strategy To Increase Productivity of The Perisai Agency System As Community Social Security - Ardi Rifai; Alm. Idqan Fahmi; Yudha Heryawan Asnawi; Suhendi Suhendi (Jurnal Aplikasi Bisnis dan Manajemen, 2025)
Background: The implementation of a community empowerment program, which involves external mobilizing agents or perisai, is anticipated to serve as a remedy for increasing participation in informal workers/ non-wage recipient workers (BPU). Nevertheless, the procedure of obtaining membership in the informal sector demonstrates erratic expansion of individuals who get non-wage benefits from BPJS Employment. Purpose: This study examines the factors that influence productivity and formulates strategies to enhance the productivity of perisai agents.Design/methodology/approach: This study adopts a quantitative causal approach, using Structural Equation Modelling (SEM) assisted by the Smart PLS statistical method (PLS-SEM)Findings/Results: The analytical findings demonstrate that the productivity of the Perisai agency system is positively and significantly influenced by four factors: organizational culture, work motivation, job satisfaction, and organizational commitment. Work motivation has the greatest indicator value and has a positive impact on increasing the productivity of Perisai agents.Conclusion: Job satisfaction within the perisai agency system exhibits the highest indicator value and significantly influences the enhancement of work productivity. Job satisfaction fosters a profound sense of trust, promoting enhanced work behavior via dedication to becoming perisai members and optimally contributing to the expansion of social security protection for informal workers.Originality/value (state of the art): BPJS Employment utilizes four criteria that directly impact production, chosen specifically to align with the company's requirements. The utilization of the PLS-SEM approach is regarded as more efficient due to its ability to reduce company expenses. Keywords: agents, influence productivity, employment, perisai agency, BPJS employment